Exercise and physical activity for people receiving peritoneal dialysis: Why not?. Issue 4 (24th March 2019) - Isnard‐Rouchon, Myriam; West, Mike; Bennett, Paul N.
Abstract: People with end‐stage kidney disease (ESKD) receiving peritoneal dialysis (PD) are physically inactive leading to low physical function and poor health outcomes. Guidelines recommend that nephrologists encourage PD patients to increase their activity levels; however, PD patients are often discouraged from participating in exercise programs because of perceived barriers and a lack of precision about the appropriate exercise regimen. This review suggests ways forward to assist nephrology professionals to encourage PD patients to exercise, instead of creating barriers. The paper draws on the literature in addition to the experience of programs in France, the United States, and Australia to demonstrate the possibilities when considering increasing physical activity in this group.